Role of cytokines in rheumatoid arthritis: an education in pathophysiology and therapeutics. - Feldmann, M; Maini, SR (2008)
SUMMARY: Advances in cDNA and monoclonal antibody technology in the 1980s fuelled the discovery and characterization of the properties of cytokines. It became apparent that because cytokines were expressed in tissues derived from autoimmune diseases, they were likely to be of fundamental importance in disease pathogenesis and developing a new class of biological therapeutics. In this review, we describe the history of bench to bedside translation of work that led to the identification of tumor necrosis factor (TNF) as a key regulator of the loss of homeostatic immune-inflammatory responses in rheumatoid arthritis (RA) and a good therapeutic target. First in human clinical trials in collaboration with a biotechnology company, the safety and efficacy of TNF blockade with a chimeric monoclonal antibody was substantiated in patients refractory to standard anti-rheumatoid drugs. Abnormal immune-inflammatory responses after therapy showed improvement and remain a focus of ongoing research in many laboratories. Longer term multi-center studies that followed with several anti-TNF biologicals have demonstrated the augmented efficacy, including inducing clinical remission, of low dose methotrexate and anti-TNF therapy co-therapy, but serious infections and lymphomas in a low frequency have been observed. In the course of the past decades, three 'blockbuster' anti-TNF biologicals are in the clinic. Over a million patients with RA and other immune-mediated diseases have been successfully treated, and a better perspective on the risk of harm and its management has become part of good clinical practice. This success has encouraged a burgeoning industry of biologicals for chronic diseases.